2009
DOI: 10.1021/es900709p
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced DNA Cleavage by α-, β-, and γ-Cyclodextrin-Bicapped C60 Supramolecular Complexes

Abstract: Water-soluble supramolecular inclusion complexes of alpha-, beta-, and gamma-cyclodextrin-bicapped C60 (CD/C60) have been investigated for their photoinduced DNA cleavage activities, with the aim to assess the potential health risks of this class of compounds and to understand the effect of host cyclodextrins having different cavity dimensions. Factors such as incubation temperature, irradiation time, and concentration of NADH or CDs/ C60 supramolecular inclusion complexes have been examined. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…The presence of a peak in the 1 H NMR spectra of compound 7f at d 8.06 to 8.22 ppm was attributed to the (NLCH) proton. The FT-IR peak between 3340-3230 cm 21 was assigned for N-H stretching and 523-529 cm 21 for the organofullerene portion in all the derivatives. The IR spectra, 1 H NMR and 13 C NMR showed that the s-triazine nitrogen has not participated in salt formation.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The presence of a peak in the 1 H NMR spectra of compound 7f at d 8.06 to 8.22 ppm was attributed to the (NLCH) proton. The FT-IR peak between 3340-3230 cm 21 was assigned for N-H stretching and 523-529 cm 21 for the organofullerene portion in all the derivatives. The IR spectra, 1 H NMR and 13 C NMR showed that the s-triazine nitrogen has not participated in salt formation.…”
Section: Resultsmentioning
confidence: 96%
“…The IR spectra of the novel compounds 5a-f showed characteristic bands of aldehyde carbonyl between 1695-1702 cm 21 and compounds 6a-f show peaks of organo fullerenes at 523-529 cm 21 . The 1 H NMR showed the presence of the pyrrolidine protons as two doublets at y5.25 ppm with coupling constants between 9.2-9.6 Hz and a singlet at y4.39 ppm.…”
Section: Resultsmentioning
confidence: 98%
“…This could mediate inflammatory responses and potentially initiate a series of toxic responses far from the initial site of deposition [21]. C60 fullerene, for example, was reported to cause photo induced DNA damage by interacting with NADH, which is an endogenously present reducing agent [189]. Similarly, carbon nanotube exposure has been associated with adverse cardiovascular effects by causing aortic DNA damage, platelet aggregation and enhanced vascular thrombosis through inflammatory events [176,190].…”
Section: Carcinogenicity Of Nanomaterialsmentioning
confidence: 99%
“…Photoinduced cleavage of super-helix DNA in pBR322 (a plasmid used E. coli cloning vectors) predominantly at guanine bases [31] was observed after incubation with carboxyfullerenes-С 60 and irradiation by visible light (but no in the darkness). CD/C 60 is also effective photosensitizers of DNA cleavage in PDT [48]. Effectiveness are increased in order of α-<, β-<, γ-CD/C 60 .…”
Section: Photoinduced Dna-cleavagementioning
confidence: 99%